Preclinical Evaluation of Nitroxide-Functionalised Ciprofloxacin as a Novel Antibiofilm Drug Hybrid for Urinary Tract Infections - Sophia Hawas; Jilong Qin; Sandra Wiedbrauk; Kathryn Fairfull-Smith; Makrina Totsika (MDPI AG, 2023)
Urinary tract infections (UTIs) are the second most common bacterial infection with high recurrence rates and can involve biofilm formation on patient catheters. Biofilms are inherently tolerant to antimicrobials, making them difficult to eradicate. Many antibiofilm agents alone do not have bactericidal activity; therefore, linking them to antibiotics is a promising antibiofilm strategy. However, many of these hybrid agents have not been tested in relevant preclinical settings, limiting their potential for clinical translation. Here, we evaluate a ciprofloxacin di-nitroxide hybrid (CDN11), previously reported to have antibiofilm activity against uropathogenic Escherichia coli (UPEC) strain UTI89 in vitro, as a potential UTI therapeutic using multiple preclinical models that reflect various aspects of UTI pathogenesis. We report improved in vitro activity over the parent drug ciprofloxacin against mature UTI89 biofilms formed inside polyethylene catheters. In bladder cell monolayers infected with UTI89, treatment with CDN11 afforded significant reduction in bacterial titers, including intracellular UPEC. Infected mouse bladders containing biofilm-like intracellular reservoirs of UPEC UTI89 showed decreased bacterial loads after ex vivo bladder treatment with CDN11. Activity for CDN11 was reported across different models of UTI, showcasing nitroxide-antibiotic hybridization as a promising antibiofilm approach. The pipeline we described here could be readily used in testing other new therapeutic compounds, fast-tracking the development of novel antibiofilm therapeutics.